Antimicrobial Synthetic and Natural Polymeric Nanofibers as Wound Dressing: A Review. Issue 6 (26th April 2022) - Parham, Shokoh; Kharazi, Anousheh Zargar; Bakhsheshi-Rad, Hamid Reza; Kharaziha, Mahshid; Ismail, Ahmad Fauzi; Sharif, Safian; Razzaghi, Mahmood; RamaKrishna, Seeram; Berto, Filippo
Abstract : Since ancient times, wound dressings have experienced many significant improvements. Evolution began using natural materials to merely cover wounds and advanced to used innovative techniques that can be customized to perform different impressive functions. Recent wound dressings, which are made of electrospun polymers, contain different active compounds, such as antimicrobial agents, that aid in wound healing and prevent dehydration and infection. The mentioned issues may influence the healing process, leading even to serious health risks for the patients. As a result, scientists are now working on novel wound bandages with improved antimicrobial properties. Electrospun polymeric nanofibers, because of their structural similarities to normal skin's extracellular matrix (ECM), bactericidal activity, and appropriateness to distribute bioactive molecules to the wound location, are regarded as good resources for enhancing skin regeneration and controlling wound infection. Herein, the latest findings on approaches for producing antimicrobial polymeric nanofibers using electrospinning and related processes are discussed. Recent advances in antibacterial biopolymeric nanofibers incorporating antimicrobial nanoparticles (silver, zinc oxide, copper oxide, etc.) are discussed. This review paper may raise significant issues, encourage additional research, and offer important insight into the potential area of antibacterial polymeric fibers. Abstract : Herein, the latest findings on approaches for producing biopolymeric nanofibers incorporating antimicrobial nanoparticles (silver, zinc oxide, copper oxide, etc.) and the primary mechanism of microbial attachment to the biopolymeric and composite fibers are evaluated in detail. This review paper may raise significant issues, and offer important insight into the potential area of antibacterial polymeric fibers.